2002
DOI: 10.1183/09031936.02.02542001
|View full text |Cite
|
Sign up to set email alerts
|

Persistent asthma: disease control, resource utilisation and direct costs

Abstract: Despite evidence that adverse outcomes are less frequent when asthma management is optimised, the link between the level of control, disease severity and medical resource utilisation (MRU) is poorly documented. This relationship was investigated in a group of patients suffering from persistent asthma (Global Initiative for Asthma (GINA) o2) in France.In 1998 a computerised family practice database was used to identify asthma patients aged 17-50 yrs. Information from the database was complemented by a patient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(109 citation statements)
references
References 21 publications
6
99
0
4
Order By: Relevance
“…Thirdly, severe asthma represents nearly 10% of all asthma cases, but up to 30% of the cost, which is mostly related to resource utilisation (e.g. unscheduled medical visits and hospitalisations) due to insufficient asthma control [5,6]. Taken together, these rather disappointing observations underscore the need for therapeutic improvement in asthma treatment.…”
mentioning
confidence: 88%
“…Thirdly, severe asthma represents nearly 10% of all asthma cases, but up to 30% of the cost, which is mostly related to resource utilisation (e.g. unscheduled medical visits and hospitalisations) due to insufficient asthma control [5,6]. Taken together, these rather disappointing observations underscore the need for therapeutic improvement in asthma treatment.…”
mentioning
confidence: 88%
“…1 The median direct health care cost in our study was lower than that reported in the United States (mean direct health care cost, US$3180) or in Europe (mean medical resource utilisation €549.8 for a controlled patient, and €1451.3 for a non-controlled patient). [21][22][23] The lower direct cost in HCMC was due to the inexpensive health care services, cheaper medications and lower hospitalisation rate when the patients used controllers. 3,13,24 The increased rate of controlled asthma in our study also contributed to the decrease in direct health care costs.…”
Section: Public Health Action Implementation Of Gina Guidelines In VImentioning
confidence: 99%
“…Indirect costs include costs resulting from missed work or school days and days with restricted activity at work, premature retirement and death. The adverse impact of asthma on the quality of life of the patients and on the families, as well as the limitation of physical, emotional and intellectual development is difficult to quantify, and therefore is referred to as intangible costs (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%